2015
DOI: 10.12924/of2015.01010003
|View full text |Cite
|
Sign up to set email alerts
|

Strategies towards Evaluation beyond Scientific Impact. Pathways not only for Agricultural Research

Abstract: Various research fields, like organic agricultural research, are dedicated to solving real-world problems and contributing to sustainable development. Therefore, systems research and the application of interdisciplinary and transdisciplinary approaches are increasingly endorsed. However, research performance depends not only on self-conception, but also on framework conditions of the scientific system, which are not always of benefit to such research fields. Recently, science and its framework conditions have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…As stated by Wolf et al "the Impact Factor and other journal-based metrics are increasingly considered inappropriate for comparing the scientific output of individuals and institutions" [48]. Furthermore, "innovation" is becoming a synonym for "patent" and has no relationship at all with the actual uptake of a solution by end-users, especially farmers.…”
Section: Discussion: Moving Through An Agroecological Innovation Paramentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Wolf et al "the Impact Factor and other journal-based metrics are increasingly considered inappropriate for comparing the scientific output of individuals and institutions" [48]. Furthermore, "innovation" is becoming a synonym for "patent" and has no relationship at all with the actual uptake of a solution by end-users, especially farmers.…”
Section: Discussion: Moving Through An Agroecological Innovation Paramentioning
confidence: 99%
“…There are new developments on this subject [48], but "these are still confronted by incentive systems that favour the old style of evaluation and old method of producing research: mono-disciplinary, with a focus on publication in international journals" [49]. National and EU Agricultural policies which support novelties and bottom-up innovations with subsidies and niche market development, if integrated with innovation policies that encourage knowledge exchange using a multi-actor approach, could facilitate a more coherent scaling up of such innovations, as is already happening in some contexts.…”
Section: Discussion: Moving Through An Agroecological Innovation Paramentioning
confidence: 99%
“…Several studies have shown the essential role of agroecological approaches, and particularly organic agriculture, for sustainable development [32][33][34]. Ecological intensification enables an improvement of productivity while at the same time reducing adverse effects on the environment [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…One of them lies in the disincentives against organic research imbued in current research evaluation [6]. Systems investigated by organic farming researchers are typically highly complex meaning that research can take longer so that research output per unit time is lower than for simpler systems.…”
Section: Published: 13 February 2017mentioning
confidence: 99%
“…Further, the interdisciplinary nature of organic research is often not favoured by the gatekeepers of specialised disciplinary science. However, there are also various developments that are slowly bringing about significant changes in the practice of research evaluation, including the open access movement, which has particular relevance for organic agriculture [6].…”
Section: Published: 13 February 2017mentioning
confidence: 99%